XML and Macromedia Flash MX. - Gubbay, Paul (XML journal :the ultimate enterprise resource.)
Over the last few years XML has become the standard for moving data across the Web. Relational databases, application servers and operating systems such .NET make XML a key part of their infrastructure and an integral part of their business plan for the future.